Brief Overview of Obesity: A Chronic Disease - Katerina A. Chremou (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
In 2017, more than 2 billion adults were overweight. Of these 650 million were obese, 39% of adults aged 18 years and over were overweight in 2016 and 13% were obese. Most of the world’s population lives in countries where overweight and obesity kill more people than malnourished. 41 million children under the age of 5 were overweight or obese in 2016. More than 340 million children and adolescents aged 5-19 were overweight or obese in 2016. According to the World Health Organization (WHO) the symptoms of obesity areIncreased appetite, Lack of feelings of food saturation, Shortness of breath, increased sweating, Rattling, Unable to deal with sudden physical activity, Feeling of daily fatigue, Back and joint pains, and Low self-esteem and self a feeling of isolation from social groups. It should be noted that the mechanisms of development of the various markers are linked to one another with the main one of the chronic inflammation. From the above, we conclude that obesity should be treated not only with Body Mass Index (BMI), but as a chronic recurrent disease, such as diabetes or hypertension, characterized by abnormally distributed or excess body fat that affects health. It requires lifelong management, like other chronic diseases and the application of medical, dietetic and behavioral techniques for timely treatment.